Exercise training undertaken within 12 months following lung resection for patients with non-small cell lung cancer (Protocol) - Cavalheri, Vinicius; Tahirah, F.; Nonoyama, M.; Jenkins, Susan; Hill, Kylie (John Wiley & Sons Ltd, 2012)
This is the protocol for a review and there is no abstract. The objectives are as follows: The primary aim of this study is to determine the effects of exercise training on exercise capacity in adults following lung resection, with or without chemotherapy, for NSCLC. The secondary aims are to determine the effects of exercise training on HRQoL, peripheral muscle force, dyspnoea and fatigue, feelings of anxiety and depression and lung function, in the same population.